Students Perception Toward the Use of Social Media in Learning English Vocabulary at Victory University of Sorong - Tupamahu, M. S.; Henukh, Tiara S.; Siahaan, Ester; M. Su, Balandina; Kogoya, Arli (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
The present study was intended to explore victory University students’ perception of social media use for English vocabulary learning. Twenty-Five students were involved in this study. The study employed a qualitative method with a case study design using questionnaires as data collection methods. Basic statistical analysis was used to analyze data from the questionnaire. The results indicated that the students in this study use social media for learning and improving their English vocabulary. They choose YouTube as the most used social media for learning English. Further, they stated that social media provides them English content sources to practice their English vocabulary. Besides, as social media provides a lot of English content, students can choose English content which they like anytime and anywhere. The situation creates a stress-free language environment for students to be comfortable and motivated to learn English outside school. Students also stated their challenge in using social media for learning, such as internet connection problems, privacy, and inappropriate content. Based on the results, it can be concluded that students have a positive perception of employing social media to learn English